2021
DOI: 10.14814/phy2.14826
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral NIRS measurements of muscle mitochondrial capacity: Feasibility and repeatability

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…The obtained ICC and CVs for day-to-day variability of vastus lateralis NIRS-derived mitochondrial power in our present study are of quite similar magnitude and strength to those reported by Hanna et al [20], Pilotto et al [28], Fennel et al [23], Beever et al [14], and Ryan et al [10], investigating the same muscle on slightly different populations and using other protocols. Additionally, the CVs of the between-day time and/or rate constants of oxygen recovery kinetics have been reported to be quite similar for another leg muscle frequently investigated, the gastrocnemius [10,12,24,34].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The obtained ICC and CVs for day-to-day variability of vastus lateralis NIRS-derived mitochondrial power in our present study are of quite similar magnitude and strength to those reported by Hanna et al [20], Pilotto et al [28], Fennel et al [23], Beever et al [14], and Ryan et al [10], investigating the same muscle on slightly different populations and using other protocols. Additionally, the CVs of the between-day time and/or rate constants of oxygen recovery kinetics have been reported to be quite similar for another leg muscle frequently investigated, the gastrocnemius [10,12,24,34].…”
Section: Discussionsupporting
confidence: 90%
“…Recreationally active young adult men (n = 11; 28.1 ± 9.7 y; 181.5 ± 6.0 cm; 79.8 ± 14.1 kg; BMI 24.1 ± 3.0; skin color type: 1 to 2 on a 5-point scale) were recruited for this study. The number of participants was chosen based on the quantity of participants recruited in similar studies (n = 10-17) [10,20,26]. This facilitates direct comparisons between studies.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, in the last decade protocols for estimating oxidative capacity of the skeletal muscle utilizing NIRS have been developed and validated. These techniques are well suited to monitor changes in muscle specific aerobic adaptations over time and thus, may enable the evaluation of the effectiveness of interventions at the muscular level (Hanna et al, 2021). Further, associations between the oxidative metabolism of the gastrocnemius muscle, utilizing NIRS during an arterial occlusion protocol, and whole-body VO 2peak have been shown (Lagerwaard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%